Challenges in Managing an Ischemic Cerebral Vascular Stroke in a Child with a Homozygote SS Sickle Cell Associated with Cerebral Palsy: A Case Study - Tanoh, Muriel Amon; Boundjike, Rosette; De-Souza, Nancy Tanya; Kadjo, Cedric Valery; Kone, Mody; Yapo-Ehounoud, Constance; Diakite, Ismaila; Tanoh, Christian; Diarra, Evelyne Aka; Assi, Berthe (European Scientific Journal, ESJ, 2024)
Introduction: Ischemic stroke is one of the most frequently observed complications of sickle cell disease. It can also be associated with cognitive impairment. These two neurological expressions of the disease can coexist in the same patient. Objective: Report a case of stroke and mental retardation in a child with homozygous SS sickle cell disease. Observation: A child aged 5 years and 8 months, homozygous sickle cell anemia, epileptic non-compliant with his antiepileptic treatment, was admitted for epileptic seizures that gradually developed over 2 months. The diagnosis of severe complicated major sickle cell syndrome was established. Discussion: The management of neurovascular, epileptic, and cognitive complications of sickle cell disease in our patient with cerebral palsy and major sickle cell disease required evaluating the risk of occurrence of severe anemia and stratification of the risk of stroke recurrence. Conclusion: Management of a major sickle cell syndrome associated with neurovascular, epileptic, and cognitive impact in a child with sickle cell disease and cerebral palsy must comply with recent recommendations.